No teens, no tech: How shortages of young workers hinder firm technology investments - Cäcilia Lipowski (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2024)
Firms in developed countries face increasing shortages of young workers. This paper studies the importance of young workers, particularly vocational trainees, for firm technology investments. Leveraging exogenous variation in trainee supply caused by an education reform in Germany in 2001, I show that a reduction in trainee supply decreases firm technology investments. This suggests complementarity between young workers and new technologies. Consistent with firms' lower opportunity costs and higher returns to training young workers than incumbents, the effect is driven by firms exposed to new tech skills. These findings dampen hopes of counteracting labor shortages by substituting labor with capital.
Keywords: D22; D24; J21; J24; O33; 330; Endogenous Technological Change; Labor Shortages; Firm Investments; Capital Adjustment Costs; Vintage-Specific Skills